ANALISIS HADIST TARBAWI TENTANG METODE PEMBELAJARAN AGAMA ISLAM (KAJIAN HADIST KONTEMPORER) - Hidayah, Nurul; Puspasetya, Titik (JoEMS (Journal of Education and Management Studies), 2021)
Analysis of Tarbawi Hadith on Learning Materials (study of Contemporary Hadith) in the world of education needs to be applied and accustomed in the school environment, as well as in the university, as well as in the community. The concept of character education in the Analysis of Hadith Tarbawi Hadith perspective is the transformation of values ​​from educators to learners directly or indirectly. In the science of Ushul al-Hadith, in terms of Hasbi al-siddieqy, the science of hadith as knowledge related to the hadith of the Prophet. As the hadith of the Prophet about the method of learning, the author uses the method of reading books about hadith and the classification of hadith. The method used by the author is qualitative. In this research method, the author found that in the book/book of tarbawi hadith written by Bukhari Umar, M.Ag, there are eight kinds of methods of learning Islam. In the method of learning Islamic education, it explains how the emotional differences need to be understood by the educator so that he is not reckless in responding to the actions of his learners, the educator should not overcome the emotional turmoil of the learners with emotional outbursts as well.